(untitled) (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2024)
Purpose: The aim of the article is to verify the impact of the use of electronic notification of deliveries on the service time of a means of transport in a distribution center. Methodology: The study used electronic notification in the form of EDI DESADV messages. The research was carried out in one of the distribution centers of a retail company operating in Poland. The study used the method of recording the time of logistics operations. The study was conducted in two stages (each lasting a week), in which the time of logistics operations was recorded in conditions without and with the DESADV message implemented. Results: The results of the conducted research show that the use of electronic despatch advice allows you to reduce the time of handling the means of transport in the distribution center. Conclusion: Reducing the time of handling the means of transport in the distribution center brings numerous additional benefits, such as faster release of the means of transport and enabling it to carry out subsequent transport tasks, handling a larger number of unloadings with the same number of resources (e.g. warehouse ramps), accelerating the internal process and enabling faster reloading to other means of transport performing the distribution process.